2016
DOI: 10.1038/onc.2016.189
|View full text |Cite
|
Sign up to set email alerts
|

LAPTM4B: an oncogene in various solid tumors and its functions

Abstract: The oncogene Lysosome-associated protein transmembrane-4β (LAPTM4B) gene was identified, and the polymorphism region in the 5′-UTR of this gene was certified to be associated with tumor susceptibility. LAPTM4B-35 protein was found to be highly expressed in various solid tumors and could be a poor prognosis marker. The functions of LAPTM4B in solid tumors were also explored. It is suggested that LAPTM4B could promote the proliferation of tumor cells, boost invasion and metastasis, resist apoptosis, initiate aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 58 publications
(65 reference statements)
1
65
1
Order By: Relevance
“…LAPTM4B (the lysosome-associated protein transmembrane-4b gene) is considered as an oncogene, and its overexpression has been proven to promote the proliferation of various tumor cells, boost invasion and metastasis, resist apoptosis, initiate autophagy, and assist drug resistance. [35][36][37][38] Overexpression of LAPTM4B in breast cancer cells results in resistance to anthracycline, and its knockdown can sensitize the drug response. 39 NGFRAP1 (nerve growth factor receptor-associated protein 1) is an apoptosisrelated gene, and its expression is downregulated in some solid organ malignancies and chronic lymphocytic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…LAPTM4B (the lysosome-associated protein transmembrane-4b gene) is considered as an oncogene, and its overexpression has been proven to promote the proliferation of various tumor cells, boost invasion and metastasis, resist apoptosis, initiate autophagy, and assist drug resistance. [35][36][37][38] Overexpression of LAPTM4B in breast cancer cells results in resistance to anthracycline, and its knockdown can sensitize the drug response. 39 NGFRAP1 (nerve growth factor receptor-associated protein 1) is an apoptosisrelated gene, and its expression is downregulated in some solid organ malignancies and chronic lymphocytic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…LAPTM4B has been identified as a direct target of miR-188-5p in PC3 and LNCaP cells (125) (Figure 4). LAPTM4B is located in late endosomes and lysosomes and can promote proliferation, invasion and inhibit apoptosis and is able to initiate autophagy (126). LAPTM4B is associated with poor prognosis and metastasis in several types of tumors (127)(128)(129)(130).…”
Section: Mir-188-5p Targets Lysosome Transmembrane Protein 4 (Laptm4b)mentioning
confidence: 99%
“…Lysosomal‐associated protein transmembrane‐4 beta (LAPTM4B) is a high‐expression gene in hepatocellular carcinoma (HCC) cells identified by fluorescent‐differential display (Shao et al ., ; Liu et al ., ; Meng et al ., ). Previous studies have identified two alleles of the LAPTM4B gene, which are differentiated from one another by an extra tandem arranged 19‐bp sequence at the 5′ untranslated region (5′UTR) in the first exon in allele*2.…”
Section: Introductionmentioning
confidence: 99%